1993
DOI: 10.1038/hdy.1993.141
|View full text |Cite
|
Sign up to set email alerts
|

Diapause in Drosophila melanogaster females: a genetic analysis

Abstract: Female Drosophila melanogaster exhibit ovarian diapause at low temperatures and short day lengths. We found that D. melanogaster isofemale lines from Windsor (Ontario, Canada) had a significantly higher percentage of females in diapause than did those from Cartersville (Georgia, U.S.A.). To investigate the heredity of this trait, we performed a 16-reciprocal cross analysis using two extreme isofemale lines called W and C. We found that diapause in D. melanogaster is inherited as a simple autosomal recessive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0
1

Year Published

1994
1994
2012
2012

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 25 publications
4
49
0
1
Order By: Relevance
“…Studies by Richard et al (1998Richard et al ( , 2001) also implicated a role for ecdysteroids in mediating vitello- genesis and the diapause response and further supported that D. melanogaster diapause is under neuroendocrine control. The expression of diapause was shown to vary both among laboratory strains and natural populations (Williams and Sokolowski 1993). stated that the characteristics of ovarian diapause in D. melanogaster indicate that the trait is of relatively recent evolutionary origin; consistent with this hypothesis, diapause expression has not been observed in either East or West African D. melanogaster strains or in D. simulans (P. Schmidt, unpubl.…”
Section: Variance For the Diapause Phenotypesupporting
confidence: 52%
See 1 more Smart Citation
“…Studies by Richard et al (1998Richard et al ( , 2001) also implicated a role for ecdysteroids in mediating vitello- genesis and the diapause response and further supported that D. melanogaster diapause is under neuroendocrine control. The expression of diapause was shown to vary both among laboratory strains and natural populations (Williams and Sokolowski 1993). stated that the characteristics of ovarian diapause in D. melanogaster indicate that the trait is of relatively recent evolutionary origin; consistent with this hypothesis, diapause expression has not been observed in either East or West African D. melanogaster strains or in D. simulans (P. Schmidt, unpubl.…”
Section: Variance For the Diapause Phenotypesupporting
confidence: 52%
“…As in endemic temperate drosophilids (e.g., Lumme and Lakovaara 1983;Kimura 1988), D. melanogaster exposed to reduced temperatures (Ͻ14ЊC) and short photoperiods (Ͻ12 h light) can undergo a form of reproductive quiescence or diapause in which oogenesis is arrested in previtellogenic stages (Saunders et al 1989;Williams and Sokolowski 1993). Diapause expression in D. melanogaster and other Drosophila results in life-span extension, elevated resistance to multiple forms of environmental stress, and reduced rates of age-specific mortality Tatar 2004).…”
mentioning
confidence: 99%
“…Flies were grown under standard conditions at 25 Ϯ 0.5°C on a 12-h light͞12-h dark (12L:12D) light cycle as described in (10). Male and female flies were collected Ͻ8 h after eclosion and placed at 11 Ϯ 0.5°C under SD conditions (10L:14D).…”
Section: Methodsmentioning
confidence: 99%
“…The Windsor (W) natural variant from Canada exhibits an autosomal-recessive high-diapause phenotype compared with the Cartersville (C) natural variant from the Southern U.S., which confers a fully dominant low-diapause phenotype (10). Crosses between the variants suggested that diapause may be influenced by relatively few genes (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation